Imaging activity-dependent regulation of neurexin-neuroligin interactions using trans-synaptic enzymatic biotinylation - Thyagarajan, Amar (2010)
The functions of trans-synaptic adhesion molecules such as neurexin and neuroligin have been difficult to study due to the lack of methods to directly detect their binding in living neurons. Here, we use Biotin Labeling of INtercellular Contacts (BLINC), a method for imaging protein interactions based on interaction-dependent biotinylation of a peptide by E. coli biotin ligase, to visualize neurexin-neuroligin trans-interactions at synapses and study their role in synapse development. We found that both developmental maturation and acute synaptic activity stimulate the growth of neurexin-neuroligin adhesion complexes, via a combination of neurexin and neuroligin surface insertion, and internalization arrest. Both mechanisms require NMDA receptor activity. We also discovered that disruption of activity-induced neurexin-neuroligin complex growth prevents recruitment of the AMPA receptor, a hallmark of mature synapses. Our results provide support for neurexin-neuroligin function in synapse maturation and introduce a general method to study intercellular protein-protein interactions.